2022
DOI: 10.1111/tid.13925
|View full text |Cite
|
Sign up to set email alerts
|

Solid organ transplantation from COVID positive donors in the United States: Analysis of United Network for Organ Sharing database

Abstract: Background Significant uncertainties remain regarding the utilization of organs for solid organ transplantation (SOT) from donors with coronavirus disease 2019 (COVID‐19). The aim of this study was to assess the trends in utilization of organs from donors with COVID‐19 and their short‐term outcomes. Methods Deceased donors between March 2020 and December 2021 with a positive COVID nucleic acid test from respiratory tract within 14 days of transplantation were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 28 publications
5
26
0
Order By: Relevance
“…Survival of patients who received grafts from COVID-19-positive donors and complications of graft dysfunction were equivalent to those who received grafts from COVID-19-negative donors [ 52 ]. Similar results were reported by Dhand et al with 193 COVID+ donors resulting in the transplantation of 281 kidneys, 106 livers and 36 hearts in 414 adult recipients [ 53 ]. A systematic review conducted with published from January 2019 to December 2021 collected information from sixty-nine recipients who received 48 kidneys, 18 livers, and 3 hearts from 57 donors with positive RTPCR for SARS-CoV-2 The investigators concluded that the use of nonpulmonary organs (kidney, liver, and heart) from SARS-CoV-2 positive donors appeared to be a safe practice, with a low risk of transmission, regardless of the presence of symptoms at the time of procurement [ 54 ].…”
Section: Lessons Learned and Experience In Sarscov-2-infected Donor R...supporting
confidence: 87%
“…Survival of patients who received grafts from COVID-19-positive donors and complications of graft dysfunction were equivalent to those who received grafts from COVID-19-negative donors [ 52 ]. Similar results were reported by Dhand et al with 193 COVID+ donors resulting in the transplantation of 281 kidneys, 106 livers and 36 hearts in 414 adult recipients [ 53 ]. A systematic review conducted with published from January 2019 to December 2021 collected information from sixty-nine recipients who received 48 kidneys, 18 livers, and 3 hearts from 57 donors with positive RTPCR for SARS-CoV-2 The investigators concluded that the use of nonpulmonary organs (kidney, liver, and heart) from SARS-CoV-2 positive donors appeared to be a safe practice, with a low risk of transmission, regardless of the presence of symptoms at the time of procurement [ 54 ].…”
Section: Lessons Learned and Experience In Sarscov-2-infected Donor R...supporting
confidence: 87%
“…Survival of patients who received grafts from COVID-19-positive donors and complications of graft dysfunction were equivalent to those who received grafts from COVID-19-negative donors [52]. Similar results were reported by Dhand et al with 193 COVID+ donors resulting in the transplantation of 281 kidneys, 106 livers and 36 hearts in 414 adult recipients [53]. A systematic review conducted with published from January 2019 to December 2021 collected information from sixty-nine recipients who received 48 kidneys, 18 livers, and 3 hearts from 57 donors with positive RT-PCR for SARS-CoV-2 The investigators concluded that the use of nonpulmonary organs (kidney, liver, and heart) from SARS-CoV-2 positive donors appeared to be a safe practice, with a low risk of transmission, regardless of the presence of symptoms at the time of procurement [54].…”
Section: Evolution Of Donation In Spain Throughout the Pandemicsupporting
confidence: 80%
“…Dear Editor, Successful use of organs from COVID positive (COVID+) donors has helped to meet the ongoing need for expansion of the donor pool. 1,2 Among some transplant centers, uncertainty remains regarding the During the study period, when compared to COVID− donors, the kidney discard rate was higher in COVID+ donors (39% vs. 33%, p = .027), the liver discard rate was not statistically different in COVID+ donors (4.3% vs. 6.3%, p = .13), and no heart discard was observed in the matched cohorts. Among the donors who led to transplantation of at least one other organ (heart, liver, intestine, or pancreas), kidney discard rate remained higher in COVID+ donors (24.6% vs. 12.1%, p < .001) (Table 1).…”
Section: Utilization and Discard Of Organs From Donors With Covid-19 ...mentioning
confidence: 99%